Kataksha [videorecording (DVD)] - Aleeha, Abu; Gabol, Mubeen; Mairaj, Saleem; Tabeir, Kiran; Khan, Kasim (Filmhub, 2025)
A news channel's crew visits the most haunting places to cover supernatural occurrences. Sallu, Ashraf, Aiman, and Nazish decide to visit Katasraj Temple in Kalar Kahar where they meet the strange character named Modi who oversees the Temple.